UKURAN DEWAN KOMISARIS, PROPORSI KOMISARIS INDEPENDEN, DAN PENGAMBILAN RISIKO BANK PADA PERUSAHAAN PERBANKAN DI INDONESIA - Rahmat Setiawan; Salsabila Barasyid; Nanda Surya Jatnika (LPSDI Bina Patria, 2025)
The purpose of this study was to determine the effect of the size of the board of commissioners and the proportion of independent commissioners on bank risk taking. The sample of this study is banking companies listed on the Indonesia Stock Exchange during the period 2007 to 2016. The number of observational data analysed was 194 data in the first model and 131 data in the second model. The analysis method used in this research is multiple linear regression. The dependent variables analysed include insolvency risk and idiosyncratic risk. And the independent variables consist of the size of the board of commissioners and the proportion of independent commissioners. The results showed that the size of the board of commissioners and the proportion of independent commissioners had a significant negative effect on bank risk taking as measured by insolvency risk and idiosyncratic risk.